Estimation of Electric Potential of X Geothermal Field Using Monte Carlo Method - Muhammad Taufiq Fathaddin (Journal of Earth Energy Science, Engineering, and Technology, 2021)
Field X is a marginal geothermal field located in the province of Maluku, Indonesia. An assessment of reservoir characteristics needs to be carried out to determine the appropriate field development method. The purpose of this study is to evaluate the electrical potential that can be generated from Field X. The Monte Carlo method is used to estimate the usable electric potential. The sensitivity of the parameters of generation time, initial temperature, and final temperature was carried out to get a wider picture. Based on the simulation results obtained a proportional relationship between reservoir temperature and electric potential. Higher reservoir temperatures can be obtained by drilling deeper wells. The most probable estimate (P50) of the electric potential of Field X is in the range of 0.141 – 0.248 MWe. An increase in the initial reservoir temperature of 15 oC causes an average increase of 16% MWe. Due to the relatively low reservoir temperature, low temperature geothermal binary power generation should be applied for field development.